Pro-angiogenic potential of human chorion-derived stem cells: in vitro and in vivo evaluation - Nur Fariha Mohd Manzor; Chua, KH; Tan, GC; Lim, YH; Hayati, AR (Wiley, 2024)
Human chorion-derived stem cells (hCDSC) were previously shown to demonstrate multipotent properties with promising angiogenic characteristics in monolayer-cell culture system. In our study, we investigated the angiogenic capability of hCDSC in 3-dimensional (3D) in vitro and in vivo angiogenic models for the purpose of future application in the treatment of ischaemic diseases. Human CDSC were evaluated for angiogenic and endogenic genes expressions by quantitative PCR. Growth factors secretions were quantified using ELISA. In vitro and in vivo vascular formations were evaluated by histological analysis and confocal microscopic imaging. PECAM-1+ and vWF+ vascular-like structures were observed in both in vitro and in vivo angiogenesis models. High secretions of VEGF and bFGF by hCDSC with increased expressions of angiogenic and endogenic genes suggested the possible angiogenic promoting mechanisms by hCDSC. The cooperation of hCDSC with HUVECS to generate vessel-like structures in our systems is an indication that there will be positive interactions of hCDSC with existing endothelial cells when injected into ischaemic tissues. Hence, hCDSC is suggested as the novel approach in the future treatment of ischaemic diseases.